2022
DOI: 10.1186/s12903-022-02228-9
|View full text |Cite
|
Sign up to set email alerts
|

Stresses induced by one piece and two piece dental implants in All-on-4® implant supported prosthesis under simulated lateral occlusal loading: non linear finite element analysis study

Abstract: Background Correct choice of the implant design and the occlusal scheme is important for the success of implant supported restorations. So, the aim of the current study was to find out the difference in the stresses induced by the one piece dental implants designed to be used in the All-on-4® concept and the conventional two piece ones under simulated lateral occlusal schemes using nonlinear finite element analysis. Methods Two finite element model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(68 reference statements)
0
3
0
1
Order By: Relevance
“…It may be concluded that OP dental implants were with a lower stress value than TP dental implants when they served in the All-on-4 implant-supported restoration of different occlusal/lateral schemes. Lower stress levels are obtained with canine-guided occlusion as compared to the group function occlusal scheme [61].…”
Section: Mohamed Et Almentioning
confidence: 92%
“…It may be concluded that OP dental implants were with a lower stress value than TP dental implants when they served in the All-on-4 implant-supported restoration of different occlusal/lateral schemes. Lower stress levels are obtained with canine-guided occlusion as compared to the group function occlusal scheme [61].…”
Section: Mohamed Et Almentioning
confidence: 92%
“…However, little is known about the differences in the biomechanical behavior of screw or cement retained prostheses. According to a previous study that compared the pre-load maintenance, stresses, and displacements of prosthetic components of screw and cement retained implant-supported crowns, the screwretained prosthesis demonstrated a higher risk of screw loosening and fracture [42].…”
Section: Crown-retention Systemmentioning
confidence: 98%
“…Furthermore, an occlusal anatomy design with reduced cusp angulation and less evident occlusal sulcus, can reduce the stress concentration and increase the fracture load for ceramic posterior crowns. Therefore, less pronounced occlusal anatomy would improve implant loading distribution and could be beneficial for the survival of the restoration [41][42][43].…”
Section: Loading Directionmentioning
confidence: 99%
“…Анализ мировой литературы и полученных научно-теоретических данных о повышении эффективности оказания ортопедической помощи пациентам с полной адентией дал возможность сформировать некоторые предложения об интерпретации сравнительной картины распределения напряжений для различных видов имплантатов с проведением дополнительных исследований методом конечных элементов [12,13,14].…”
unclassified